SOIL CONTROLLING FACTORS OF METHANE GAS PRODUCTION FROM FLOODED RICE FIELDS IN PATI DISTRICT, CENTRAL JAVA - P. Setyanto; Rosenani A.B.; A.K. Makarim; Che Fauziah I.; A. Bidin; Suharsih Suharsih (Indonesian Journal of Agricultural Science, 2002)
Atmospheric methane (CH4) is recognized as one of the most important greenhouse gases. Methane, with some 15-30 times greater infrared-absorbing capability than CO2 on a mass basis, may account for 20% of anticipated global warming. Soils are one of the key factors, which play an important role in CH4 production and emission. However, data on CH4 emission from different soil types and the characteristics affecting CH4 production are lacking when compared to data on agronomic practices. This study was conducted to investigate the potential of CH4 production of selected soils in Java, and determine the limiting factors of CH4 production. The results showed that addition of 1% glucose to the soils led to an increase in CH4 production by more than twelve fold compared to no glucose addition. The CH4 production potential ranged between 3.21 and 112.30 mg CH4 kg-1 soil. The lowest CH4 production potential occurred in brown-grayish Grumosol, while the highest was in dark-gray Grumosol. Chemical and physical properties of the soils have great influence on CH4 production. Stepwise multiple regression analysis of CH4 production and soil characteristics showed that pH and the contents of Fe2O3, MnO2, SO4, and silt in the soil strongly influenced CH4 production. Results of this study can be used for further development of a model on CH4 emission from rice fields.